Using Islamic Films to Foster Anti-Corruption Values: An Arabic Classroom-Based Study at an Indonesian Islamic University - A. Fajar Awaluddin; Agustan Agustan (Langkawi: Journal of The Association for Arabic and English, 2023)
Several studies have examined the cultivation of students in developing anti-corruption value awareness; however, there is still scarce study on anti-corruption value education mediated by Islamic warrior films. This study presents class-based research to examine how Islamic films increase knowledge of anti-corruption values. this paper to examine the use of Umar bin Khattab's Islamic film to promote anti-corruption values. Thirty-eight students of the Arabic Language Education Study Program volunteered as participants in this study. The data were collected from student worksheets, class observations, notes of in-class discussions, and semi-structured interviews. The finding indicates that using four major themes were identified: (1) Awareness of anti-corruption values; (2) Students' perceptions of the effectiveness of anti-corruption values; (honest, fair, and firm leadership values); (3) Propagation of anti-corruption values; and; (4) The importance of anti-corruption values in the film to contemporary social realities. Additionally, this study is hoped to inspire film-mediated learning to foster other values, including moral and cultural values. the empirical findings of this research will shed light on the usage of film as an educational tool for fostering other values such as morals, culture, etc. The research limitation in this study is the extent to which classroom-based instructional videos influence the cultivation of anti-corruption values.